The Intersection of Thought on Hadīth Methodology: Mahmūd Abu Rayyah’s Critique and Musthafa Al-Sibā’ī’s Defense - Zainuddin, Moch; Anam, Wahidul (LPPM IAIN Kudus, 2025)
This study aims to analyze the common ground in the methodology of Hadīth criticism proposed by Mahmūd Abu Rayyah and the defense presented by Musthafa Al-Sibā’ī. These include criticism of the authenticity of hadīth, criticism of the concept of ‘adalah al-shahabah, criticism of Hadīth narrators, and the relation between Hadīth and the Qur’an. Mahmūd Abu Rayyah is known as one of the figures who was critical of the validity of Hadīth and highlighted the aspects of transmission that he considered less robust. On the other hand, Musthafa Al-Sibā’ī emerged as a safeguard of the Hadīth tradition, emphasizing the importance of Hadīth authenticity in the structure of Islamic law and teachings. Through a descriptive-comparative approach, this study explores the backgrounds, critical methods, and defense arguments of the two figures and explores possible points of convergence between them. This study reveals that although fundamental comparisons exist in the approaches and views of the two scholars, their methodologies present complementary dimensions that, when synthesized, offer a more nuanced paradigm for evaluating ḥadīth authenticity in contemporary or modern contexts. It includes the importance of the scientific study of the Sunnah, the need to understand the Sunnah in its historical context, the recognition of the Sunnah’s hermeneutical relationship with Qur’anic exegesis, the criticism of the misuse of Hadīth, the need to contextualize the Sunnah in the Modern era and the influence of modernism.